Recycle Performance of Heterogeneous Catalyst Metal Oxides-Based Layered Double Hydroxide for Oxidative Desulfurization Process of 4-methyldibenzothiophene - Ahmad, Nur; Rohmatullaili, Rohmatullaili; Hanifah, Yulizah; Wibiyan, Sahrul; Amri, Amri; Wijaya, Alfan; Mardiyanto, Mardiyanto; Mohadi, Risfidian; Royani, Idha; Lesbani, Aldes (Bulletin of Chemical Reaction Engineering & Catalysis, 2023)
The desulfurization of oil must be resolved as soon as possible due to a variety of issues, including environmental contamination and protection regulations. It was believed that oxidative desulfurization (ODS) was the most promising method. In this research, metal oxide-based layered double hydroxides (TiO2@Ni-Al and ZnO@Ni-Al) were effectively synthesized for the ODS of 4-methyldibenzothiophene (4-MDBT). TiO2@Ni-Al and ZnO@Ni-Al exhibited superior catalytic performance and high recycling capacity, achieving a 99% removal rate after five reactions in 30 min. The heterogeneous catalyst TiO2@Ni-Al/ZnO@Ni-Al is easy to separate and recover from a reaction system. Increased temperature facilitates the transformation of 4-MDBT into 4-MDBTO2. The influence of H2O2's rapid decomposition rate, which can inhibit oxidation reactions, reduces the catalytic activity as the temperature increases. 4-MDBT Sulphur removal on TiO2@Ni-Al and ZnO@Ni-Al is 99.48 and 99.51%, respectively. TiO2@Ni-Al and ZnO@Ni-Al have great potential for use in the industry based on these results. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).